Epilepsy is a disease! - Walter Oleschko Arruda (Arquivos de Neuro-Psiquiatria)
According to the definition of disease, epilepsy shall not be considered neither a symptom nor a syndrome. Epilepsy is a generic term for a group of diseases characterized by seizures. It implies a state quite distinct from health. Therefore it seems worthy to keep epilepsy as such in the International Classification of Diseases (ICD).